2002
DOI: 10.1159/000063568
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-Four-Hour QT Interval Variability: Increased QT Variability during Sleep in Patients with Panic Disorder

Abstract: Recent studies on beat-to-beat QT interval variability (QTV) have shown that it can be used as a noninvasive measure of cardiac repolarization lability. It is also a predictor of sudden cardiac death and is higher in patients with anxiety and depression. This study examined the diurnal measures in QTV in 32 normal adults and 22 patients using 24-hour electrocardiogram records. We obtained 8 5-min segments of ECG sampled at 1,000 Hz from the 24-hour records. Our results show that QTV measures at nighttime are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 35 publications
3
21
0
Order By: Relevance
“…First, an elevated QTVi and elevated NE spillover have been independently found in postinfarction patients and in patients with PD and depression (2,20,22,25). Second, activation of cardiac sympathetic activity (by orthostatic challenge or isoproterenol infusion) leads to increase in QTVi (23).…”
Section: Discussionmentioning
confidence: 99%
“…First, an elevated QTVi and elevated NE spillover have been independently found in postinfarction patients and in patients with PD and depression (2,20,22,25). Second, activation of cardiac sympathetic activity (by orthostatic challenge or isoproterenol infusion) leads to increase in QTVi (23).…”
Section: Discussionmentioning
confidence: 99%
“…[55][56][57][58][59] Circadian rhythm is characteristic for QTc as well. [60][61][62][63][64][65][66] Figure 4 shows pooled, individually corrected (as described earlier) QT intervals before treatment vs the clock time in 26 unrelated healthy individuals from the previously presented data.…”
Section: Circadian Rhythm In Qt and Qtcmentioning
confidence: 99%
“…Effective anti-panic treatment has been suggested to increase heart rate variability (Garakani et al 2008;Tucker et al 1997), and may thus potentially decrease the risk of cardiac mortality. Studies have also found increased QT variability in PD patients (Sullivan et al 2004;Yeragani et al 2002a;Yeragani et al 2000), reflecting an abnormal ventricular repolarisation, which may lead to malignant ventricular arrhythmias and sudden cardiac death (Adamson and Vanoli 2001). …”
Section: Somatic -Cardiacmentioning
confidence: 99%